Manufacturing process of easy-to-clean antibacterial ceramic product

By combining modified Elosite powder with nano-titanium dioxide antibacterial agent, the problem of poor dispersion of antibacterial agents in ceramic products is solved, and the efficient antibacterial and easy-to-clean properties of ceramic products are achieved.

CN119490365AActive Publication Date: 2025-02-21GUANGDONG DEBAO TECH IND CO LTD

Patent Information

Application Number
CN202411673647.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The dispersion of silver-based antibacterial agents in the glaze of ceramic products leads to a reduced antibacterial effect. The micropores inside the ceramics are prone to absorb dirt and difficult to completely clean.

Method used

Modified Elosite powder is used to combine with nanotitanium dioxide silver antibacterial agent, and the use of silane coupling agent is ensured to be evenly dispersed in the glaze slurry, and it is firmly adhered to the ceramic surface by high temperature firing.

Benefits of technology

It improves the antibacterial properties and durability of ceramic products, while enhancing the ease of cleanliness and smoothness of the glaze, avoiding stains and bacterial seepage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146522270000131
    Figure BDA0005146522270000131
  • Figure BDA0005146522270000141
    Figure BDA0005146522270000141
Patent Text Reader

Abstract

The invention discloses a manufacturing process of an easy-to-clean antibacterial ceramic product, and belongs to the technical field of ceramic product production. The preparation process comprises the following steps: mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, carrying out wet ball milling by using flint cobblestones to prepare premixed glaze slip, sanding to prepare glaze slip I, uniformly spraying the glaze slip I on a ceramic green body, and drying in a drying kiln to form a substrate glaze surface; mixing modified halloysite and deionized water II, carrying out wet ball milling and sanding by using the flint cobblestones to prepare glaze slip II, uniformly spraying the glaze slip II on the glaze surface of the substrate, standing, feeding into a tunnel kiln, and carrying out primary firing to obtain the easy-to-clean antibacterial ceramic product. The glaze surface is smoother and more compact, the easy-cleaning performance of the glaze surface is improved, the antibacterial agent is firmly attached to the glaze surface, the antibacterial durability is enhanced, and the antibacterial performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic product production, and in particular relates to a manufacturing process of an easy-to-clean antibacterial ceramic product. Background Art

[0002] Glaze is a silicate compound that adheres to the surface of the body after high temperature heating. Glaze coating ceramic products can provide them with rich colors and textures, increase their decorative effects and artistic value, and make them more attractive and beautiful; at the same time, glaze coating on the surface of ceramic products can form a protective film, increase the hardness and wear resistance of ceramic products, avoid deformation or cracking under high temperature conditions, and effectively prevent external factors from eroding and damaging ceramic materials, such as anti-stain, acid and alkali corrosion, etc. In addition, glaze can make the surface of ceramic products flat and smooth, reduce its adsorption of dirt, and make them easier to clean and hygienic.

[0003] Although the surface of ceramic products looks smooth, there are still tiny pores inside them. These pores can absorb liquids and dirt, making it difficult to completely remove stains when cleaning. In addition, the main component of ceramic glaze is silicate. The high surface activity of silicate easily adsorbs other substances, including silver-based antibacterial agents. When the silicate material comes into contact with a solution containing a silver-based antibacterial agent, the active sites on the silicate surface adsorb silver ions to form silver agglomeration, which makes the antibacterial agent less dispersed and difficult to adhere to the glaze of ceramic products, reducing the antibacterial effect. Summary of the invention

[0004] The invention discloses a manufacturing process of an easy-to-clean antibacterial ceramic product, and belongs to the technical field of ceramic product production. The preparation process comprises the following steps: mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to obtain premixed glaze slurry, sand milling to obtain glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, loading into a drying kiln for drying, and forming a substrate glaze surface; mixing modified halloysite and deionized water II, wet ball milling with the flint pebbles, sand milling to obtain glaze slurry II, spraying the glaze slurry II evenly on the substrate glaze surface, letting it stand, and sending it into a tunnel kiln for one-time firing to obtain the easy-to-clean antibacterial ceramic product.

[0005] The technical problem to be solved by the present invention is to prepare easy-to-clean antibacterial ceramic products, improve the easy-to-clean performance and antibacterial durability of the glaze, and improve the antibacterial performance.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A manufacturing process for an easy-to-clean antibacterial ceramic product, the manufacturing process comprising the following steps:

[0008] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare a premixed glaze slurry, sand milling to prepare a glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2-3 hours to form a substrate glaze surface;

[0009] (2) The modified halloysite powder and deionized water II are mixed, wet-milled with the flint pebbles to obtain a mixed slurry, sand-milled to obtain a glaze slurry II, and the glaze slurry II is evenly sprayed on the glaze surface of the substrate, allowed to stand for 3-5 hours, and sent into a tunnel kiln for one-time firing at 1025-1065° C. to obtain the easy-to-clean antibacterial ceramic product.

[0010] As a preferred technical solution of the present invention, the mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 10-15: 5-8: 2-6: 10-15: 4-10: 50-70: 26.45-70.6: 113.4-272.8: 10.2-10.8.

[0011] As a preferred technical solution of the present invention, in step (1), the grinding time is 5-8h; the sieve mesh is 120-200 mesh; the median particle size of the premixed glaze slurry obtained after wet ball milling is less than or equal to 50 microns; the median particle size of the glaze slurry I obtained after sand milling is less than or equal to 0.1 microns; and the drying temperature is 95°C.

[0012] As a preferred technical solution of the present invention, in step (2), the time of the primary firing is 3-6 hours; the median particle size of the mixed slurry obtained after the wet ball milling is less than or equal to 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is less than or equal to 0.1 microns.

[0013] As a preferred technical solution of the present invention, the preparation of the modified halloysite powder comprises the following steps:

[0014] (11) centrifugally separating and purifying halloysite, grinding to obtain halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A;

[0015] (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B;

[0016] (13) adding the dispersion A and the dispersion B to a reactor, adding p-toluenesulfonic acid, stirring, and reacting at a controlled temperature. After the reaction is completed, centrifuging the reaction solution, washing the precipitate, centrifuging again, extracting, and drying to obtain a carrier;

[0017] (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically vibrating to prepare an antibacterial agent dispersion;

[0018] (15) Take the carrier and antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40° C., and add the silane coupling agent dropwise while stirring. After the addition is completed, add ammonia water, stir, dry, and grind to obtain the modified halloysite powder.

[0019] As a preferred technical solution of the present invention, in step (11), the mass ratio of the halloysite powder to toluene is 0.2-0.4:40; and the ultrasonic dispersion time is 1-2h.

[0020] As a preferred technical solution of the present invention, in step (12), the mass ratio of polyethylene glycol to toluene is 1-1.2:40; and the ultrasonic dispersion time is 30-40 min.

[0021] As a preferred technical solution of the present invention, in step (13), the mass ratio of the dispersion A, dispersion B and p-toluenesulfonic acid is 2-3:2-3:1-2; the stirring time is 0.5-1h; and the temperature-controlled reaction refers to reacting at 150-155°C for 3h.

[0022] As a preferred technical solution of the present invention, in step (14), the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 2-3:60-70; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes.

[0023] As a preferred technical solution of the present invention, in step (15), the mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 1-2:55-65:0.5-0.8:0.02-0.06:40; the concentration of the ammonia water is 13.38 mol / L; and the silane coupling agent is 3(2,3-epoxypropoxy)propyltrihydroxysilane.

[0024] Beneficial effects of the present invention:

[0025] (1) The manufacturing process of an easy-to-clean antibacterial ceramic product disclosed in the present invention can fill the micropores and gaps in the ceramic glaze by adding halloysite, so that the glaze particles are arranged more closely to form a dense structure, which effectively prevents the penetration of foreign substances such as stains and bacteria, prevents stains and bacteria from penetrating into the interior of the ceramic, and improves the anti-seepage performance of the glaze and ceramic products. At the same time, the dense structure can also enhance the smoothness and improve the surface texture and touch of the ceramic products.

[0026] (2) The manufacturing process of an easy-to-clean antibacterial ceramic product disclosed in the present invention modifies halloysite by introducing hydrophilic groups on the Al side of the halloysite to improve its hydrophilicity and making the Si side hydrophobic, so that the modified halloysite powder has a lower tendency to agglomerate and aggregate, is easy to be evenly dispersed in the solvent, improves the fluidity of the glaze slurry, makes the glaze surface more uniform and smooth, and can also make the antibacterial agent more evenly dispersed in the glaze slurry. The effective dispersion of the antibacterial agent can avoid the growth of microorganisms and improve the antibacterial properties of the ceramic product.

[0027] (3) The manufacturing process of an easy-to-clean antibacterial ceramic product disclosed in the present invention is to modify halloysite by first introducing a hydrophilic functional group bonding to the Al-based side of the halloysite to avoid binding with the antibacterial agent, and at the same time, the hydrophobic side of the Si-based halloysite is outwardly attached to the antibacterial agent through a silane coupling agent, and the antibacterial agent is firmly fixed on the surface, so that the antibacterial property of the glaze of the prepared ceramic product is improved, and the density and smoothness of the surface of the product are improved;

[0028] Furthermore, during the high-temperature calcination process, the silane coupling agent forms a strong chemical bond with the Si-based side of the halloysite surface, filling and sealing the pores and microcracks inside the ceramic, making the antibacterial agent more firmly attached to the glaze surface, having good durability, being able to effectively inhibit bacterial growth for a long time, and improving the antibacterial durability. DETAILED DESCRIPTION

[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0030] Example 1

[0031] Preparation of modified halloysite powder:

[0032] (11) centrifugally separating and purifying halloysite, grinding, and obtaining halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; the mass ratio of the halloysite powder to toluene is 0.2:40; and the ultrasonic dispersion time is 1 hour;

[0033] (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B; the mass ratio of polyethylene glycol to toluene is 1:40; and the ultrasonic dispersion time is 30 min;

[0034] (13) Add the dispersion A and dispersion B to a reactor, add p-toluenesulfonic acid, stir, and react under temperature control. After the reaction, centrifuge the reaction solution, wash the precipitate, centrifuge again, extract, and dry to obtain a carrier; the mass ratio of the dispersion A, dispersion B, and p-toluenesulfonic acid is 2:2:1; the stirring time is 0.5 h; the temperature control reaction refers to reacting at 150° C. for 3 h;

[0035] (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically oscillating to obtain an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 2:60; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes;

[0036] (15) Take the carrier and antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40°C, add the silane coupling agent dropwise while stirring, add ammonia water after the addition is complete, stir, dry, and grind to obtain the modified halloysite powder; the mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 1:55:0.5:0.02:40; the concentration of the ammonia water is 13.38 mol / L; the silane coupling agent is 3(2,3-epoxypropoxy)propyltrihydroxysilane.

[0037] Preparation of easy-to-clean antibacterial ceramic products:

[0038] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2 hours to form a substrate glaze surface; the grinding time is 5 hours; the sieve mesh is 120 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.1 microns; the drying temperature is 95° C.;

[0039] (2) Mixing modified halloysite powder and deionized water II, wet ball milling with the flint cobblestone to obtain a mixed slurry, sand milling to obtain glaze slurry II, spraying the glaze slurry II evenly on the glaze surface of the substrate, letting it stand for 3 hours, and sending it into a tunnel kiln for one-time firing at 1025° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 3 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.1 microns;

[0040] The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 10:5:2:10:4:50:26.45:113.4:10.2; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0041] Example 2

[0042] Preparation of modified halloysite powder:

[0043] (11) centrifugally separating and purifying halloysite, grinding to obtain halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; the mass ratio of the halloysite powder to toluene is 0.3:40; and the ultrasonic dispersion time is 1.5 h;

[0044] (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B; the mass ratio of polyethylene glycol to toluene is 1.1:40; and the ultrasonic dispersion time is 35 min;

[0045] (13) Add the dispersion A and dispersion B to a reactor, add p-toluenesulfonic acid, stir, and react under temperature control. After the reaction, centrifuge the reaction solution, wash the precipitate, centrifuge again, extract, concentrate, and dry to obtain a carrier. The mass ratio of the dispersion A, dispersion B, and p-toluenesulfonic acid is 2.5:2.5:1.5. The stirring time is 0.7 h. The temperature control reaction refers to reacting at 153° C. for 3 h.

[0046] (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically oscillating to obtain an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol is 2.5:65; the stirring time is 30 minutes; the ultrasonic oscillation time is 30 minutes;

[0047] (15) Take the carrier and antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40°C, add the silane coupling agent dropwise while stirring, add ammonia water after the addition is complete, stir, dry, and grind to obtain the modified halloysite powder; the mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 1.5:60:0.65:0.04:40; the concentration of the ammonia water is 13.38 mol / L; the silane coupling agent is 3(2,3-epoxypropoxy)propyltrihydroxysilane.

[0048] Preparation of easy-to-clean antibacterial ceramic products:

[0049] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, loading into a drying kiln and drying for 2.5 hours to form a substrate glaze surface; the grinding time is 6 hours; the sieve mesh is 180 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 40 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.08 microns; the drying temperature is 95° C.;

[0050] (2) Mixing modified halloysite powder and deionized water II, wet ball milling with the flint cobblestone to obtain a mixed slurry, sand milling to obtain glaze slurry II, spraying the glaze slurry II evenly on the glaze surface of the substrate, letting it stand for 4 hours, and sending it into a tunnel kiln for one-time firing at 1045° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 5 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 40 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.08 microns;

[0051] The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 12:6:4:12:6:60:50:200:10.6; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0052] Example 3

[0053] Preparation of modified halloysite powder:

[0054] (11) centrifugally separating and purifying halloysite, grinding to obtain halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; the mass ratio of the halloysite powder to toluene is 0.4:40; and the ultrasonic dispersion time is 2 h;

[0055] (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B; the mass ratio of polyethylene glycol to toluene is 1.2:40; and the ultrasonic dispersion time is 40 min;

[0056] (13) Add the dispersion A and dispersion B to a reactor, add p-toluenesulfonic acid, stir, and react under temperature control. After the reaction is completed, centrifuge the reaction solution, wash the precipitate, centrifuge again, extract, and dry to obtain a carrier; the mass ratio of the dispersion A, dispersion B, and p-toluenesulfonic acid is 3:3:2; the stirring time is 1 hour; the temperature control reaction refers to reacting at 155°C for 3 hours;

[0057] (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically oscillating to obtain an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 3:70; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes;

[0058] (15) Take the carrier and antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40°C, add the silane coupling agent dropwise while stirring, add ammonia water after the addition is complete, stir, dry, and grind to obtain the modified halloysite powder; the mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 2:65:0.8:0.06:40; the concentration of the ammonia water is 13.38 mol / L; the silane coupling agent is 3(2,3-epoxypropoxy)propyltrihydroxysilane.

[0059] Preparation of easy-to-clean antibacterial ceramic products:

[0060] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 3 hours to form a substrate glaze surface; the grinding time is 8 hours; the sieve mesh is 200 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 30 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.06 microns; the drying temperature is 95° C.;

[0061] (2) Mixing modified halloysite powder and deionized water II, wet ball milling and sand milling with the flint cobblestone to obtain glaze slurry II, spraying the glaze slurry II evenly on the glaze surface of the substrate, letting it stand for 5 hours, and sending it into a tunnel kiln for one-time firing at 1065° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 6 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 30 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.06 microns;

[0062] The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 15:8:6:15:10:70:70.6:272.8:10.8; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0063] Comparative Example 1

[0064] Preparation of modified halloysite powder:

[0065] (11) centrifugally separating and purifying halloysite, grinding, and obtaining halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; the mass ratio of the halloysite powder to toluene is 0.2:40; and the ultrasonic dispersion time is 1 hour;

[0066] (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B; the mass ratio of polyethylene glycol to toluene is 1:40; and the ultrasonic dispersion time is 30 min;

[0067] (13) Add the dispersion A and dispersion B to a reactor, add p-toluenesulfonic acid, stir, and react under temperature control. After the reaction, centrifuge the reaction solution, wash the precipitate, centrifuge again, extract, and dry to obtain a carrier; the mass ratio of the dispersion A, dispersion B, and p-toluenesulfonic acid is 2:2:1; the stirring time is 0.5 h; the temperature control reaction refers to reacting at 150° C. for 3 h;

[0068] (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically oscillating to obtain an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 2:60; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes;

[0069] (15) The carrier and antibacterial agent dispersion are added to anhydrous ethanol, and then ammonia water is added. The mixture is stirred, dried, and ground to obtain the modified halloysite powder. The mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, and ammonia water is 1:55:0.5:40. The concentration of the ammonia water is 13.38 mol / L.

[0070] Preparation of easy-to-clean antibacterial ceramic products:

[0071] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2 hours to form a substrate glaze surface; the grinding time is 5 hours; the sieve mesh is 120 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.1 microns; the drying temperature is 95° C.;

[0072] (2) Mixing modified halloysite powder and deionized water II, wet ball milling with the flint cobblestone to obtain a mixed slurry, sand milling to obtain glaze slurry II, spraying the glaze slurry II evenly on the glaze surface of the substrate, letting it stand for 3 hours, and sending it into a tunnel kiln for one-time firing at 1025° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 3 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.1 microns;

[0073] The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 10:5:2:10:4:50:26.45:113.4:10.2; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0074] Comparative Example 2

[0075] Preparation of modified halloysite powder:

[0076] (11) centrifugally separating and purifying halloysite, grinding, and obtaining halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; the mass ratio of the halloysite powder to toluene is 0.2:40; and the ultrasonic dispersion time is 1 hour;

[0077] (12) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically oscillating to obtain an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 2:60; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes;

[0078] (13) Take the dispersion A and the antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40°C, add the silane coupling agent dropwise while stirring, add ammonia water after the addition is complete, stir, dry, and grind to obtain the modified halloysite powder; the mass ratio of the dispersion A, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 1:55:0.5:0.02:40; the concentration of the ammonia water is 13.38 mol / L; the silane coupling agent is 3(2,3-epoxypropoxy)propyltrihydroxysilane.

[0079] Preparation of easy-to-clean antibacterial ceramic products:

[0080] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2 hours to form a substrate glaze surface; the grinding time is 5 hours; the sieve mesh is 120 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.1 microns; the drying temperature is 95° C.;

[0081] (2) Mixing modified halloysite powder and deionized water II, wet ball milling with the flint cobblestone to obtain a mixed slurry, sand milling to obtain glaze slurry II, spraying the glaze slurry II evenly on the glaze surface of the substrate, letting it stand for 3 hours, and sending it into a tunnel kiln for one-time firing at 1025° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 3 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.1 microns;

[0082] The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles, and deionized water II is 10:5:2:10:4:50:26.45:113.4:10.2; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0083] Comparative Example 3

[0084] Preparation of antimicrobial dispersion:

[0085] The nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol are mixed, stirred, and ultrasonically vibrated to prepare an antibacterial agent dispersion; the mass ratio of the nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol is 2:60; the stirring time is 30 minutes; the ultrasonic vibration time is 30 minutes;

[0086] Preparation of easy-to-clean antibacterial ceramic products:

[0087] (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare premixed glaze slurry, sand milling to prepare glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2 hours to form a substrate glaze surface; the grinding time is 5 hours; the sieve mesh is 120 mesh; the median particle size of the premixed glaze slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry I obtained after the sand milling is 0.1 microns; the drying temperature is 95° C.;

[0088] (2) mixing halloysite powder and deionized water II, wet-ball milling with the flint cobblestone to obtain a mixed slurry, sand-milling to obtain a glaze slurry II, spraying the glaze slurry II uniformly on the substrate glaze surface, and continuing to uniformly spray an antibacterial agent dispersion on the substrate glaze surface after spraying the glaze slurry II, standing for 3 hours, and sending it into a tunnel kiln for one-time firing at 1025° C. to obtain the easy-to-clean antibacterial ceramic product; the one-time firing time is 3 hours; the median particle size of the mixed slurry obtained after the wet ball milling is 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is 0.1 microns;

[0089] The mass ratio of potassium feldspar, quartz, calcite, halloysite powder, wollastonite, frit, deionized water I, flint pebbles, deionized water II: antibacterial agent dispersion is 10:5:2:10:4:50:26.45:113.4:10.2:0.5; the chemical composition of the frit is as follows: 1 mass part R2O: 9 mass parts CaO: 1 mass part BaO: 8 mass parts ZnO: 2 mass parts PbO: 7 mass parts Al2O3: 0.5 mass parts B2O3: 56 mass parts SiO2: 2.4 mass parts ZrO.

[0090] Performance Testing

[0091] The easy-to-clean performance test was carried out according to the standard GB / T 31859-2015;

[0092] The antibacterial performance test was carried out according to the standard JC / T 897-2014.

[0093] The ceramic glazes prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to the above standards. The test results are shown in Table 1 below:

[0094] Table 1

[0095]

[0096]

[0097] It can be seen from the test results in Table 1 that the ceramic product glazes prepared in Examples 1-3 have good easy-to-clean performance and antibacterial performance; the ceramic product glaze prepared in Comparative Example 1 on the basis of Example 1 has a decreased easy-to-clean performance, and the antibacterial performance is significantly reduced. The reason may be that no silane coupling agent is added during the preparation process, resulting in poor adhesion rate of the antibacterial agent under high-temperature calcination, making the surface density of the ceramic body lower than that of Example 1, resulting in reduced easy-to-clean performance; the ceramic product glaze prepared in Comparative Example 2 on the basis of Example 1 has a significantly decreased easy-to-clean performance, and the antibacterial performance is lower than that of Comparative Example 1. The reason may be that the dispersion performance of halloysite powder is poor, which makes the dispersibility of the antibacterial agent poor, resulting in lower surface density of the ceramic body, lower easy-to-clean performance and antibacterial performance; the ceramic product prepared in Comparative Example 3 on the basis of Example 1 has worse halloysite powder dispersion performance than Comparative Example 2, and the antibacterial agent adhesion rate is lower, resulting in worse easy-to-clean performance and antibacterial performance than Comparative Example 2.

[0098] Note: The nano titanium dioxide silver antibacterial agent powder (model ZM-T30A) involved in this application is from Hangzhou Zheming New Materials Co., Ltd.

[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A manufacturing process for easy-to-clean antibacterial ceramic products, characterized in that: The preparation process comprises the following steps: (1) mixing potassium feldspar, quartz, calcite, wollastonite and frit, grinding, sieving, adding deionized water I, wet ball milling with flint pebbles to prepare a premixed glaze slurry, sand milling to prepare a glaze slurry I, spraying the glaze slurry I evenly on the ceramic green body, placing it in a drying kiln and drying it for 2-3 hours to form a substrate glaze surface; (2) The modified halloysite powder and deionized water II are mixed, wet-milled with the flint pebbles to obtain a mixed slurry, sand-milled to obtain a glaze slurry II, and the glaze slurry II is evenly sprayed on the glaze surface of the substrate, allowed to stand for 3-5 hours, and sent into a tunnel kiln for one-time firing at 1025-1065° C. to obtain an easy-to-clean antibacterial ceramic product.

2. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 1, characterized in that: The mass ratio of potassium feldspar, quartz, calcite, modified halloysite powder, wollastonite, frit, deionized water I, flint pebbles and deionized water II is 10-15: 5-8: 2-6: 10-15: 4-10: 50-70: 26.45-70.6: 113.4-272.8: 10.2-10.

8.

3. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 1, characterized in that: In step (1), the grinding time is 5-8h; the sieve mesh is 120-200 mesh; the median particle size of the premixed glaze slurry obtained after wet ball milling is less than or equal to 50 microns; the median particle size of the glaze slurry I obtained after sand milling is less than or equal to 0.1 microns; and the drying temperature is 95°C.

4. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 1, characterized in that: In step (2), the primary firing time is 3-6 hours; the median particle size of the mixed slurry obtained after the wet ball milling is less than or equal to 50 microns; the median particle size of the glaze slurry II obtained after the sand milling is less than or equal to 0.1 microns.

5. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 1, characterized in that: The preparation of the modified halloysite powder comprises the following steps: (11) centrifugally separating and purifying halloysite, grinding to obtain halloysite powder, and ultrasonically dispersing the halloysite powder in toluene to obtain dispersion A; (12) ultrasonically dispersing polyethylene glycol in toluene to prepare dispersion B; (13) adding the dispersion A and the dispersion B to a reactor, adding p-toluenesulfonic acid, stirring, and reacting at a controlled temperature. After the reaction is completed, centrifuging the reaction solution, washing the precipitate, centrifuging again, extracting, and drying to obtain a carrier; (14) mixing nano titanium dioxide silver antibacterial agent powder and anhydrous ethanol, stirring, and ultrasonically vibrating to prepare an antibacterial agent dispersion; (15) Take the carrier and antibacterial agent dispersion and add them to anhydrous ethanol, heat them in a water bath at 40° C., and add the silane coupling agent dropwise while stirring. After the addition is completed, add ammonia water, stir, dry, and grind to obtain the modified halloysite powder.

6. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 5, characterized in that: In step (11), the mass ratio of the halloysite powder to toluene is 0.2-0.4:40; and the ultrasonic dispersion time is 1-2 hours.

7. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 5, characterized in that: In step (12), the mass ratio of polyethylene glycol to toluene is 1-1.2:40; and the ultrasonic dispersion time is 30-40 min.

8. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 5, characterized in that: In step (13), the mass ratio of the dispersion A, dispersion B and p-toluenesulfonic acid is 2-3:2-3:1-2; the stirring time is 0.5-1h; and the temperature-controlled reaction refers to reacting at 150-155°C for 3h.

9. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 5, characterized in that: In step (14), the mass ratio of the nano titanium dioxide silver antibacterial agent powder to anhydrous ethanol is 2-3:60-70; the stirring time is 30 minutes; and the ultrasonic oscillation time is 30 minutes.

10. The manufacturing process of the easy-to-clean antibacterial ceramic product according to claim 5, characterized in that: In step (15), the mass ratio of the carrier, anhydrous ethanol, antibacterial agent dispersion, silane coupling agent, and ammonia water is 1-2: 55-65: 0.5-0.8: 0.02-0.06: 40; the concentration of the ammonia water is 13.38 mol / L; and the silane coupling agent is 3 (2,3-epoxypropoxy) propyl trihydroxysilane.

Citation Information

Patent Citations

  • Copper ion-loaded halloysite nanotube antimicrobial agent and preparation method thereof

    CN101999414A

  • Hygroscopic antistatic polyester fiber preparation method

    CN108018617A

  • High-temperature-resistant antibacterial ceramic and preparation method thereof

    CN108569889A

  • Foam concrete based on high-stability foaming agent and preparation method of foam concrete

    CN112279675A

  • Silane coupling agent modified halloysite nanotube loaded antibacterial agent compound, polycarbonate composition and preparation method and application thereof

    CN114213713A

Cited By

  • Antibacterial antifouling ceramic material and preparation method thereof

    CN121135148A

  • Antibacterial and antifouling ceramic material and preparation method thereof

    CN121135148B